ABUNDANCES OF COPPER AND ZINC IN STARS OF THE GALACTIC THIN AND THICK DISKS - Gorbaneva, T. I.; Mishenina, T. V.; Basak, N. Yu.; Soubiran, C.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2008)
The spectra of studied stars were obtained with the ELODIE spectrograph at the 1.93-m telescope of the Observatoire de Haute Provence (France). The determination of Cu and Zn abundances was carried out in LTE assumption by model atmosphere method, for Cu the hyperfine structure was taken into account. Cu and Zn abundance trends for thin and thick disk's stars are presented.